Effect of Rock Phosphate Enriched With Sp36 to Soybean Yield on Ultisol Lampung - Wijanarko, Andy; Taufiq, Abdullah (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2011)
Research to study the effect of application of rock phosphate (RP) enriched with SP36 to soybean on Ultisol was conducted at ILETRIs' green house from July to October 2008. Treatment consisted of combination of rock phosphate from Lamongan and Bojonegoro at rates of 162 kg P2O5/ha with three rates of SP36 (0, 9, 18 and 27 kg P2O5/ha). The treatments were arranged in randomized complete block design and replicated three times. The result showed that application of RP from Lamongan and Bojonegoro to Ultisol Lampung at rates of 162 kg P2O5/ha increased soil pH by 0.3 and 0.5, available P (Bray 1) by 400% and 823% respectively compared to check.Highest soybean yield was attained by application of RP from Lamongan combined with SP36 at rates of 18 kg P2O5/ha or RP from Bojonegoro combined with SP36 at rates of 9 kg P2O5/ha which yielded 4.98 and 5.21 g/pot respectively. This result indicated that RP from Lamongan and Bojonegoro can be applied directly as P fertilizer for soybean in acid soil, and combining them with SP36 will increase their effectiveness.Keywords: rock phosphate, SP36, soybean, ultisol